2015
DOI: 10.1097/pec.0000000000000386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rapid Intravenous Rehydration in Children With Mild-to-Moderate Dehydration

Abstract: We conclude that, in children with mild-to-moderate dehydration, the administration of 20 mL/kg per hour for 2 hours of 0.9% saline solution + 2.5% glucose improved clinical scores and may be used as an alternative and safe way for intravenous rehydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…Fluid treatment is usually performed with either balanced crystalloid fluids or iso‐oncotic colloids, such as plasma and 5% albumin. Because crystalloids quickly equilibrate between both the intravascular and interstitial volumes, they are mainly used to treat dehydration and temporary volume deficits . Iso‐oncotic colloids remain in the intravascular volume for a prolonged period; thus, they are often preferred when long‐lasting plasma volume expansion is desired…”
Section: Introductionmentioning
confidence: 99%
“…Fluid treatment is usually performed with either balanced crystalloid fluids or iso‐oncotic colloids, such as plasma and 5% albumin. Because crystalloids quickly equilibrate between both the intravascular and interstitial volumes, they are mainly used to treat dehydration and temporary volume deficits . Iso‐oncotic colloids remain in the intravascular volume for a prolonged period; thus, they are often preferred when long‐lasting plasma volume expansion is desired…”
Section: Introductionmentioning
confidence: 99%
“…8 The median ketone level in our cohort was higher than demonstrated by Levy et al and Janet et al (4.4 mmol/L versus 3.1 mmol/L and 1.5 mmol/L, respectively). 6,9 In our study, 73% of patients had a POC ketone levels >3 mmol/L and blood testing showed features of acidosis in 46% (n=38/83) (blood pH <7.3 or plasma bicarbonate <18 mmol/L). The cohort's hospital admission rate (30%) was noticeably elevated compared to our baseline admission rate for children with the ED diagnosis of gastroenteritis (20%) which reflects the selective inclusion criteria which isolated children with clinically significant manifestation of symptoms.…”
Section: Discussionmentioning
confidence: 45%
“…This decrease is similar to the decrease of 0.2 mmol/L/hr noted by Janet et al in children rehydrated with 20 mL/kg over 2 hours of normal saline and 2.5% dextrose followed by 120 mL of oral rehydration solution. 6 There is no international consensus for the optimal rehydration fluids in children. 19 We believe that the significance of ketosis in the presentation of acute paediatric illness and the potential for tailored treatments in paediatric acute illness warrants further research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations